Theoretical modeling of magnetic field effects on the optical properties of type-II core–shell quantum dot - Holovatsky, Volodymyr; Holovatskyi, Ihor; Chubrei, Maryna; Duque, Carlos (Applied Nanoscience V.13, p.7125–7133 (2023), 2023)
This study presents a simple model within the efective mass approximation to describe the magnetic feld impact on the energy structure and interband optical quantum transitions in type-II ZnTe/CdSe and CdSe/ZnTe spherical quantum dots. The dependencies energy spectra and wave functions of an electron and hole on the magnetic feld are calculated by the diagonalization method for spherical quantum dots of diferent sizes. It is shown that the magnetic feld violates the spherical symmetry of the system and takes of the degeneration of the energy spectrum concerning the magnetic quantum number. For QD ZnTe/CdSe, the energy of the electron, and for QD CdSe/ZnTe, the energy of the hole in the states with m ≥ 0 increases when the magnetic feld enhances; for the states with m < 0, these dependences are non-monotonous (decreasing at frst and then increasing). Moreover, the ground state of an electron for QD ZnTe/CdSe and the ground state of a hole for QD CdSe/ZnTe are formed alternately by the lowest states m = 0,−1,−2, … with increasing the induction of magnetic feld (Aharonov–Bohm efect). The dependencies of the oscillator strength and the quantum energy transition on magnetic feld induction are calculated.
Keywords: Core–shell quantum dot · Type-II band alignment · Quasiparticle energy spectrum · Quasiparticle wave function · Oscillator strength · Quantum transition · Magnetic feld